Sex related coronary plaque progression patterns among patients with family history as the sole cardiovascular risk factor: A PARADIGM sub-study - Conte, Edoardo; Lee, Sang-Eun; Chang, Hyuk-Jae; Hadamitzky, Martin; Kim, Yong-Jin; Pontone, Gianluca; Budoff, Matthew J.; Gottlieb, Ilan; Lee, Byoung Kwon; Chun, Eun Ju; Cademartiri, Filippo; Maffei, Erica; et al. (Atherosclerosis, 2025)
How sex may influence the prevalence and progression of coronary atherosclerosis in patients with positive family history for CAD is still unclear. Aim of the present study was to explore the role of family history of CAD in coronary atherosclerosis expression and progression in male and female subjects. A total of 2252 patients who underwent clinically indicated serial CCTAs at an interscan interval of more than 2 years were enrolled in the PARADIGM Study. For the present sub-analysis, a selected population was identified after applying the following exclusion criteria:1)uncomplete plaque analysis data; 2)occurrence of any MACE between CT scans; 3) positive history for coronary artery disease before the first CT scan; 4) the presence of any traditional risk factors a part from positive family history of CAD. Subjects enrolled were classified according to family history of CAD status and separate analysis for male and female were performed. Among 210 subjects finally enrolled, no differences in annual total plaque progression according to family history of CAD were detected even when plaque subtypes were evaluated. On the contrary, an higher annual fibrous-fatty plaque progression was evident only among male subjects with family history of CAD [0.3 mm3(IQR 0–3.7) vs 0 mm3(IQR -0.5–0.9), p = 0.0302 for patients with vs without family history respectively] but not among female. At multivariate analysis significative annual fibrous-fatty plaque progression was recorded only among male with family history [OR 3.29(95 % CI 1.05–10.35),p = 0.0412]. Family history of CAD resulted to be associated with rapid high risk plaque volume progression among males but not among females. [Display omitted] •This study addressed the role of family history of CAD in coronary atherosclerosis progression, according to sex.•Family history of CAD is associated with high-risk plaque volume progression only among male.•Present data highlight the importance of a sex-specific approach to coronary atherosclerosis progression.